Randomised controlled trial of a sexual risk reduction intervention for STI prevention among men who have sex with men in the USA. (12th April 2017) - Eaton, Lisa A; Kalichman, Seth C; Kalichman, Moira O; Driffin, Daniel D; Baldwin, Robert; Zohren, Larissa; Conway-Washington, Christopher
Abstract : Objectives: Novel interventions to address sexual risk taking and slow rates of STIs are urgently needed, in particular among black men who have sex with men (MSM) in the USA. Serosorting, or limiting condomless sex acts to partners of the same HIV status, is commonly practised among MSM, yet can lead to STI and remains largely unaddressed by public health agencies. Methods: A two-arm, randomised controlled trial was conducted from 2012 to 2015. This trial assessed the effects of a single-session, sexual partner selection and risk decision intervention (experimental arm) versus a single-session, Centers for Disease Control and Prevention-based, sexual risk reduction intervention (control arm) on psychosocial measures, sexual risk taking and STI. Results: At study follow-ups, multiple beneficial changes were observed on sexual risk beliefs measures (ie, changes in serosorting and condom use beliefs, and HIV risk perceptions) and sexual risk taking among the experimental arm relative to the control arm. Overall main effects, however, of the intervention on STI outcomes on year-long follow-ups were non-significant. There was evidence for short-term effects on STI outcomes, and self-report of multiple STIs and STI symptoms demonstrated positive effects over the follow-up period. Conclusions: Brief interventions to address sexual risk taking can result in short-term beneficial outcomes and can be incorporated into currently existing infrastructure at healthcare agencies. Additional intervention will be necessary for demonstrating long-term results. Trial registration number: NCT02128594 .